(untitled) (Semiárida, 2018)
This study involved the assessing of agamic propagation of Junellia succulentifolia (Kuntze) Moldenke by using stakes collected in spring and autumn from three plant populations of Northern Patagonia. The same mother plants were used in both collection seasons. Treatments of stakes with naphthalene acetic acid (ANA) at different concentrations were assayed. Results indicate that stakes collected in spring and applied 100 ppm of ANA had higher rooting index and shoot growth than the rest of treatments tested that included autumn stakes, ANA at 250 ppm, or no addition of hormone. It is concluded that agamic propagation of such species is possible, although with variable results amongst plant populations. These variations could result from differences in age of mother plants.